2016
DOI: 10.3892/ol.2016.4227
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings of malignant bilateral carotid body tumors: A case report and review of the literature

Abstract: Abstract. Carotid body tumors (CBTs) are a rare type of extra-adrenal paraganglioma, which originate from the carotid body. A 29-year-old woman was admitted to the Department of Head and Neck Surgery, Beijing Tongren Hospital (Capital Medical University, Beijing, China) with hoarseness of the throat, which had progressively worsened over seven months. The patient had a family history of CBTs. Computed tomography and ultrasound imaging revealed multiple well-enhanced masses located at the bilateral carotid bifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…MCBTs mainly metastasize to regional nodes, particularly those in the IIA region around the tumor [12]. Some CBTs can also metastasize to the lung, bone, liver, breast, pancreas, thyroid, kidney, and brain [5]. Jin et al [15] suggested that when a patient is diagnosed with MCBT, neck dissection is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCBTs mainly metastasize to regional nodes, particularly those in the IIA region around the tumor [12]. Some CBTs can also metastasize to the lung, bone, liver, breast, pancreas, thyroid, kidney, and brain [5]. Jin et al [15] suggested that when a patient is diagnosed with MCBT, neck dissection is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…MCBTs generally require postoperative radiotherapy, while chemotherapy is generally ineffective [17]. Although the malignant risk is relatively low among CBTs, all CBTs should be viewed as having malignant potential [18]. However, whether it is necessary to perform intraoperative level IIA lymph node dissection during surgery remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrent laryngeal nerve was correctly visualized but involved in the mass. So we have not the choice to sacrifice the nerve to avoid any remaining mass tissue [8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The major morbidity is related to the intraoperatively cranial nerve lesion. The risk of cranial nerve palsy as a complication of CBT surgery has been reported to range from 10% to 40% [5,15,41]. The use of clamping of all carotid arteries with placement of shunt and the immediate replacement or repair of damaged vessel, can reduce clearly massive bleeding, cerebrovascular accidents and overall morbidity [44].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Among the possible germline mutations, those affecting succinate dehydrogenase complex iron sulfur subunit B have been associated with greater paraganglioma aggressiveness and a higher risk of metastatic disease. Despite the fact that paragangliomas are considered benign lesions, a small proportion of the affected patients develop lymph node or distant metastases ( 4 , 5 ) . In addition to their capacity for dissemination to local and distant lymph nodes, paragangliomas can metastasize to the bone, lungs, and liver by hematogenous spread.…”
Section: Introductionmentioning
confidence: 99%